Blood Group O Protect End-Stage Renal Disease Patients With Dialysis From Coronary Artery Disease - Ye, Zixiang; Wu, Yaxin; Tu, Yimin; Chen, Mulei; Gao, Yanxiang; Shi, Linying; Li, Peizhao; Xie, Enmin; Guo, Ziyu; Li, Qing; Yu, Xiaozhai; Li, Yike; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective Our study aims to investigate the role of the ABO blood group in the development and severity of coronary artery disease (CAD) in end-stage renal disease (ESRD) patients with dialysis. Methods A total of 408 ESRD patients with dialysis between January 2010 and December 2020 were enrolled including 204 patients diagnosed with CAD undergoing coronary angiography for the first time, and baseline characteristics as well as Gensini score (GS) were collected. Logistic regression analysis and linear regression analysis were performed to evaluate the relation of ABO blood types to the risk and severity of CAD, respectively. Results Blood group O frequency was significantly low in dialysis ESRD patients with CAD (25 vs. 38.24%) compared with the non-CAD patients and multivariable logistic regression showed blood group O was negatively associated with the risk of CAD [adjusted odds ratio (OR) = 0.33, 95% CI = 0.19–0.60, p < 0.001] as well as the GS tertiles (adjusted OR = 0.23, 95% CI = 0.11–0.49, p < 0.001) compared with A blood group. Blood group A, B, and AB were positively associated with the high Gensini tertile compared with O blood group (adjusted OR = 4.26, 95% CI = 2.03–8.93, p < 0.001; adjusted OR = 2.39, 95% CI = 1.11–5.13, p < 0.05; adjusted OR = 4.33, 95% CI = 1.40–13.35, P < 0.05). Similarly, multivariable linear regression results revealed O blood type was negatively associated with the GS (β = −26.129, 95% CI = −40.094 to −12.164, p < 0.001). Conclusion This case-control study demonstrated that blood group O was a potential independent protective factor for the risk and severity of CAD in ESRD patients with dialysis.